Skill up; gradation of anganwadi workers pertaining to growth chart plotting and interpretation in rural areas of Varanasi district, India - Prabha, Chandra; Srivastava, Ratan Kr.; Gupta, Manoj Kumar (International Journal of Research in Medical Sciences, 2019)
Background: The task of using the growth chart by Anganwadi Workers (AWWs) for growth monitoring requires technical skill. It was hypothesized that skill up-gradation can make a difference in the performance of AWWs in regard with growth monitoring. The aim of the study was to evaluate the effect of intervention in improving skill of AWWs regarding growth chart plotting and interpretation. Methods: It was a field based interventional study, which was conducted in rural areas of Varanasi district, India. A total of 66 AWWs each from Chiraigaon (intervention) and Cholapur (control) community development blocks of Varanasi district was selected for the study. Each AWW was provided 3 weight readings of different ages for plotting and 4 filled growth charts for interpretation. Chi square test has been applied to assess the significant difference. Results: Only around 10% of AWWs could correctly plot all 3 growth charts and similar proportion of AWWs could also correctly interpret all 4 filled growth charts. The planned intervention could significantly improve their skill of growth chart plotting and interpretation and during end line survey 41% and 77% of AWWs could correctly plot all 3 growth charts and interpret all the four growth charts, respectively. Conclusions: The developed hypothesis is proved, and intervention was found effective in significantly improving the skills of AWWs in regard with growth monitoring.